Analisis Kemampuan Koneksi Matematika Siswa pada Materi Teorema Pythagoras Ditinjau dari Gaya Kognitif di Kelas VIII SMP Negeri 1 Jatiroto Tahun Ajaran 2016/2017 - Sari, Ayu Shita; , Rita P. Khotimah, S.Si, M.Sc (2017)
Mathematical connections ability is one of basic skills that important to be mastered by students. Students with mathematical connections ability will have a better understanding of learning mathematics. This study aims to analyze and describe students's mathematical connections ability on Pythagorean theorem material viewed from cognitive style in the eighth grade of SMP Negeri 1 Jatiroto academic year 2016/2017. This type of research is based on qualitative research approach. This research subject is four eighth-B grade students of SMP Negeri 1 Jatiroto, consists of 2 students with field dependent (FD) cognitive style and 2 students with field independent (FI) cognitive style. Data collection technique that used is cognitive style test with group Embedded Figure Test (GEFT) instrument, mathematical connections ability test, interviews and documentation. Data analysis technique is done through data reduction, data display, and conclusion drawing. Data validity by using triangulation techniques. The results showed that indicator to understand relationship between different mathematical topics can be achieved by students with FD cognitive style and students with FI cognitive style. Indicator to apply mathematics in solving everyday life problems can be achieved by students with FI cognitive style, however students with FD cognitive style still made some errors. Indicator to apply relationship between mathematical topics and other disciplines topics only can be achieved by students with FI cognitive style, however students with FD cognitive style cannot achieved the indicator.